Crystal clear: How leaders and coworkers together shape role clarity and well‐being for employees in social care - Zettna, Nate; Yam, Cheryl; Kunzelmann, Arian; Forner, Vivien; Dey, Shanta; Askovic, Mina; Johnson, Anya; Nguyen, Helena; Jolly, Anupama; Parker, Sharon K. (2024)
Working in social care is fraught with challenges fueled by changing policies, funding structures, societal expectations, and high relational demands, leaving employees in this sector particularly vulnerable to poor well-being. In this study, we focus on the importance of a supportive work context—specifically coworker instrumental support and leaders' role clarity—in enabling employee role clarity, and how this can foster better mental health and reduce fatigue from ongoing changes in the sector. We ran a multilevel moderated mediation model on a sample of 270 social care employees matched with 47 leaders across two disability care organizations in Australia. Results showed that coworker instrumental support promotes role clarity, which in turn is associated with lower psychological distress and change fatigue, and higher job satisfaction. The positive relationship between coworker instrumental support and role clarity, and the subsequent relationships with well-being, were stronger when employees had leaders who themselves had role clarity. Our findings highlight the importance of a supportive work context and role clarity as malleable levers in enabling a sustainable social care workforce and provide new theoretical and practical insights for human resource management in the social care sector.